A Complex Interplay: Cognitive Behavioural Therapy for Severe Health Anxiety in Addison's Disease to Reduce Emergency Department Admissions. Issue 4 (10th April 2017) - Daniels, Jo; Sheils, Elizabeth
Abstract : Background: Addison's disease (AD) is a rare chronic illness caused by adrenocortical insufficiency. Due to the pivotal role of the regulating hormone cortisol in AD, there is a common symptom overlap between the presentation of anxiety and adrenal crisis. Previous literature has identified the prevalence of anxiety in endocrinological disorders, however there is a paucity of research examining the complex interplay between AD and anxiety.Aims: This paper describes a single case study of a patient with severe health anxiety and co-morbid AD. The aims of the study were to establish if standard cognitive behavioural therapy for health anxiety in AD can lead to a reduction in psychological distress, and whether this approach is an effective intervention for the reduction of Emergency Department admissions.Method: A single case design was used, with pre- and post-measures of health anxiety, general anxiety and depression. Data on Emergency Department admissions prior to and following treatment were used to assess change in this domain.Results: Reliable and clinically significant reductions were seen across all measures, from severe to sub-clinical levels. There was a complete amelioration of Emergency Department admissions in the 12 months following completion of treatment.Conclusions: This preliminary study provides a sound rationale for further research into AD complicated by anxiety. Findings support the clinical utility of the cognitive behavioural therapy model for complex presentations of AD, offering a potential treatment option where anxiety is elevated and interfering with self-management and leading to high levels of health service use.